Analisis Perkembangan Industri Kreatif di Kecamatan Jekan Raya: Tinjauan Terhadap Faktor-Faktor Pendukung dan Tantangan Menuju Pertumbuhan Berkelanjutan - Jepri Jepri; Risdayanti Risdayanti; Amisha Patel Pardede; Laura Purnama; Alfin Rabil Awalam; Suherman Suherman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of writing this work is to analyze the development of the creative industry in Jekan Raya District, reviewing the supporting factors and challenges towards sustainable growth. uses qualitative methods to detail the development of the creative industry in Jekan Raya District, utilizing in-depth interviews, direct observation and documentation. Using a triangulation approach, data is analyzed thematically to reveal the supporting factors and challenges faced by the creative industry in the region. The research results provide an in-depth understanding of the local dynamics of the creative industry, opening up opportunities for further development and strengthening the creative ecosystem in the sub-district. The result of this work is the development of creative industries in Jekan Raya District, such as oyster mushroom cultivation, culinary lemang, and salted egg production, reflecting the harmonious integration of tradition and innovation. The success of these MSME players is supported by creativity, patience, and the use of social media as a marketing strategy. Despite facing challenges related to creative skills training and infrastructure, the synergy between the government and MSME players is expected to optimize the growth of the creative industry, make a positive contribution to the local economy, and create job opportunities for the local community.